Evaluating the effects of land management policy on waterbird habitats in the Liaohe River Delta wetland - Haozheng Dong; Houlang Duan (International Journal of Digital Earth)
The effects of land use change on waterbird habitat have not been thoroughly studied. We used the PLUS model and InVEST model, remote sensing data, and waterbird monitoring data to explore changes in habitat for geese, ducks, shorebirds, gulls, and cranes and storks between 1980 and 2041 in the Liaohe River Delta wetland. The year 2015 was the turning point of habitat quality change. Significant decreases in mean habitat quality and high-quality habitat area from 1980 to 2015 were observed for most waterbird groups; no significant changes in habitat quality and area were observed between 2015 and 2023. The mean habitat quality and high-quality habitat area increased under the future government control scenario but decreased under the natural development scenario between 2023 and 2041. A marked change from high-quality habitat to low-quality habitat from inland areas to the sea was observed between 1980 and 2015, which stemmed from intensive land reclamation. The effects of land reclamation were stronger on crane and stork, gull, and shorebird habitat than on goose and duck habitat. Conservation of existing habitats and the restoration of degraded wetlands for different waterbirds will be necessary to ensure that their habitat requirements are met.